THE INFLUENCE OF STUDENT ACCOMMODATION ON DIETARY PATTERNS, ACTIVITY AND ALCOHOL CONSUMPTION: EXPERIENCES FROM NMMU - Gresse, Annelie; Steenkamp, Liana; Pietersen, Jacques (South African Journal of Higher Education, 2016)
Leaving home to study together with changes in living arrangements may contribute to unhealthy lifestyles in higher education students. The objectives of this study were to describe eating patterns, physical activity and alcohol use among students at the Nelson Mandela Metropolitan University (NMMU) in the context of student accommodation. A convenience sample (n=619) participated in a cross-sectional electronic self-administered survey after providing informed consent. Of the 257 students who regularly skip meals, significantly more were residing in hostels than in other accommodation. Hostel students also reported a significantly lower consumption of fruit, vegetables and dairy products, with 25% indicating insufficient funds as reason. An inactive lifestyle was reported by 49% (n=296) of participants As long-term health can be affected by lifestyle choices, these findings can be used in intervention strategies to improve behaviour. The researchers recommend that an investigation be undertaken into the social problems that may contribute to risk, especially in hostel students.